Bibliometric Analysis of Online Learning in the Era of Technological Progress - Albet Karuniawan; Eko Risdianto (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2023)
In the era of technological advances, much learning has been shifted to online learning. This has led to many educational researchers researching and writing on topics about online learning in the era of technological progress. Therefore, researchers will conduct a bibliometric analysis of online learning in the era of technological progress to find out how online learning is implemented in the era of technological progress. The research method is a literature review using bibliometric analysis. The first step in this research is determining keywords. Then proceed with an initial search based on the specified keywords. After that, the data obtained was filtered and collected based on the group. After filtering the data, initial statistical data was compiled. Then, the data that has been compiled is analyzed to obtain results. After getting the results, visualization is carried out using VosViewer to get an overview of the data that has been obtained. The results of this research show that online learning is divided into 3 clusters, namely the first cluster is online learning and education, the second cluster is Covid, and the third cluster is online learning and the Covid pandemic period. It can be concluded that online learning is a form of distance learning or training that utilizes technology as a telecommunication tool such as the internet and other devices. It has been widely implemented since the onset of the Covid-19 pandemic in Indonesia. The implementation of online learning has gone well, but there are still many shortcomings.